Meditação, grupos e terapia ocupacional: uma abordagem autobiográfica do Projeto Presença - Lambais, Gabriela (Universidade Federal de São Carlos, 2023)
Starting university can be a time of several changes for young people, concerning their daily life, support networks and educational dynamics. This context can be harmful to students' mental health, making it necessary to promote health care practices. Meditation is a practice that can improve everyday life. Objectives: this study aimed to systematize the experience of creating and conducting a meditation project offered between 2018 and 2023; analyze the experience as a group device, meeting, learning, and welcoming, considering professional training in occupational therapy degree. Methodology: a qualitative study with an autobiographical approach was conducted using narrative and reflective descriptions. The analysis of the experience was performed using references from the Encounter Group (by Carl Rogers) and the Operative Group (by Enrique Pichon-Rivière). Results: the narrative made it possible to recall events, records, and photos based on the construction of a timeline containing professional training movements during graduation, in-depth studies in the field, and the process of meditation meetings. The Presença Project emerged from individual initiatives and collective interests in meditation in the university environment. Studies on meditation techniques were sought to support the continuity of meetings over time. During the project, the initiative was expanded to other contexts. Discussion: In association with Pichon’s inverted cone learning process, aspects of care that contributed to the learning of meditative techniques were identified, such as the environment, group management, relevance of events, moments of sharing, and interpersonal cooperation. The development of empathy, congruence, and unconditional acceptance (Rogers) were fundamental in allowing the group to be led with more freedom and intuition, based on personal and undergraduate life experiences. Conclusion: The training process in occupational therapy contributed to the foundation of knowledge about group theories, therapeutic bond construction, and the development of a singularized care process. Institutional support, such as research support grants, favored dedication to deepening studies and improving the project. In this case, it was observed that groupality is composed of a constant interaction within the person, group, and coordination. In the case of the Presença Project, meditation was a determining factor in forming bases for bonding, groupality, and the development of care strategies in the university daily context.
Meditation, groups and occupational therapy: an autobiographical approach of Presença Project
Keywords: Meditação; Universidades; Promoção da saúde; Grupos de encontro; Terapia ocupacional; Meditation; Universities; Health promotion; Sensitivity training groups; Occupational therapy; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; CIENCIAS DA SAUDE::SAUDE COLETIVA; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA SOCIAL::PROCESSOS GRUPAIS E DE COMUNICACAO; CIENCIAS DA SAUDE::SAUDE COLETIVA::MEDICINA PREVENTIVA